Social Skills as a Mediator Between Secure Attachment and Peer Relationships - Pan, Yinghao; Zhang, Wei; Iskandar, Amirul (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective:  This study aimed to examine the mediating role of social skills in the relationship between secure attachment and peer relationships among Chinese adolescents.Methods and Materials: A descriptive correlational design was used with a sample of 419 high school students aged 14 to 18 from urban regions in China, selected based on Morgan and Krejcie’s sampling table. Participants completed three standardized instruments: the Inventory of Parent and Peer Attachment (IPPA), the Social Skills Rating System (SSRS), and the Peer Relations Questionnaire (PRQ). Data were analyzed using Pearson correlation in SPSS-27 to explore bivariate relationships among the variables, and Structural Equation Modeling (SEM) in AMOS-21 to assess the mediating role of social skills. Model fit was evaluated using multiple indices including χ²/df, CFI, GFI, AGFI, RMSEA, and TLI.Findings: The results indicated significant positive correlations between secure attachment and social skills (r = .61, p < .001), secure attachment and peer relationships (r = .54, p < .001), and social skills and peer relationships (r = .66, p < .001). SEM results showed a good model fit (χ² = 112.78, df = 48, χ²/df = 2.35, CFI = 0.97, RMSEA = 0.057). Social skills significantly mediated the relationship between secure attachment and peer relationships, with a direct effect (β = 0.31, p < .001), an indirect effect through social skills (β = 0.40, p < .001), and a total effect (β = 0.71, p < .001).Conclusion: Secure attachment plays a critical role in shaping peer relationships during adolescence, and this relationship is partially mediated by social skills. Enhancing social competencies in adolescents may help translate early emotional security into stronger and more positive peer connections.